PENDIRIAN BANK SAMPAH PADA KELOMPOK IBU RUMAH TANGGA di DESA JATITENGAH, BOJONEGORO - Shochrul Rohmatul Ajija; Muryani Muryani; Sylva Alif Rusmita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2020)
Jatitengah Village is one of the villages located in Sugihwaras District, Bojonegoro Regency. The main problem being faced by Jatinegara village is poverty and waste. The community is less able to manage waste properly. Much garbage is thrown in the garden or rice field. Seeing these conditions the establishment of a waste bank is very important to do, so that people are aware of a healthy and clean environment. In addition the community can increase income through waste management. There are 4 (four) outcomes of this program. Among them are 1) publications in ISSN journals; 2) publication in print / electronic mass media; 3) video of the activity; and 4) availability of adequate facilities and infrastructure of the waste bank and the operation of the waste bank properly.